Processamento hidrotérmico da casca de soja visando a obtenção de açúcares fermentescíveis, bio-óleo e hidrocarvão - Draszewski, Crisleine Perinazzo (2025)
In this thesis, soybean hulls were subjected to different hydrothermal processes, including steam explosion and subcritical hydrolysis/hydrothermal liquefaction, in a multipurpose unit that was assembled for the development of this work. The pretreatment by steam explosion, with and without an acid catalyst (0.5% w/w H₂SO₄), was carried out at different residence times to obtain a cellulose-rich solid, reaching up to 98% w/w. The best condition for this pretreatment, corresponding to 180 °C, under 5 MPa, for 5 minutes, was integrated with subcritical hydrolysis (230 and 260 °C, solvent/feed ratio S/F of 40 and 80) in the same unit, in a single experimental run, only modifying the pressure and temperature conditions. High-performance liquid chromatography analyzed the obtained liquid to quantify fermentable sugars, organic acids, and inhibitors. A fermentable sugar yield of 19.19 ± 0.49 g/100 g of soybean hulls at 230 °C and S/F-80 was achieved in the integrated process, representing a 3.3- fold increase compared to the yield obtained from untreated biomass. Semi-continuous hydrothermal processing was also applied to raw soybean hulls at different temperatures (230, 260, 300, and 340 °C) and the same ratios were evaluated in the integrated processing. Extraction with dichloromethane separated bio-oil, with a maximum yield of 30.72 ± 0.18 g/100 g of hulls at 260 °C and S/F-80. The study also evaluated kinetic profiles and characterized the solid (hydrochar) and liquid (bio-oil) products, highlighting their higher heating values, which reached 30.14 ± 0.11 MJ/kg for hydrochar and 24.86 ± 0.09 MJ/kg for bio-oil.